"Digital tools will never take the place of a good teacher": understanding teachers' resistance to using technology through Glasser's Choice Theory. (1st July 2019) - Wilson, Anat; Fuhrman, Orly; Turner, Kristina
The development of adaptive technologies presents new challenges regarding teachers' resistance to the use of technology and questions their role and autonomy. This paper presents findings from a qualitative case study with a group of Australian teachers who trialled a new reading comprehension tool developed by the Centre for Educational Technology, Israel. Drawing on notions from Glasser's Choice Theory, findings emerged to be aligned with five basic needs: 1) a need for survival in a changing workplace; 2) a need to be free from disturbances and free to make one's own choices; 3) needing to feel a sense of professional belonging; 4) a need for power over what students do and over how learning is experienced; 5) and, the need for enjoying work and fun in learning. The paper puts forward a call to further explore teacher-training through a Choice Theory framework.